2006
DOI: 10.1159/000090808
|View full text |Cite
|
Sign up to set email alerts
|

The continuing quest to comprehend genomic imprinting

Abstract: The discovery of the phenomenon of genomic imprinting in mammals showed that the parental genomes are functionally non-equivalent. Considerable advances have occurred in the field over the past 20 years, which has resulted in the identification and functional analysis of a number of imprinted genes the expression of which is determined by their parental origin. These genes belong to many diverse categories and they have been shown to regulate growth, complex aspects of mammalian physiology and behavior. Many a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 103 publications
1
19
0
Order By: Relevance
“…The high degree of purity of equid trophoblast preparations compared with placental isolations from mice may have reduced false-positive assignments caused by contaminating maternal tissues and facilitated the detection of paternal-expression bias in this extraembryonic lineage. This paternal-expression bias of imprinted genes is consistent with the early experiments in mouse embryo manipulation (8,37). Furthermore, our data provide a list of candidate genes that could produce the pattern of eCG levels in maternal serum described long ago for pregnant equids carrying intra-and interspecies pregnancies (17).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The high degree of purity of equid trophoblast preparations compared with placental isolations from mice may have reduced false-positive assignments caused by contaminating maternal tissues and facilitated the detection of paternal-expression bias in this extraembryonic lineage. This paternal-expression bias of imprinted genes is consistent with the early experiments in mouse embryo manipulation (8,37). Furthermore, our data provide a list of candidate genes that could produce the pattern of eCG levels in maternal serum described long ago for pregnant equids carrying intra-and interspecies pregnancies (17).…”
supporting
confidence: 87%
“…Paternally Expressed Imprinted Genes Predominate in Placenta. The discovery of imprinting through the construction of androgenetic and gynogenetic mice strongly suggested that the paternal genome has a major influence on placental development (8,37). Similar conclusions can be drawn from tissue development in human molar pregnancies (38,39).…”
mentioning
confidence: 62%
“…3,4 Imprinted genes encode either proteins or noncoding RNA (ncRNA), the majority of which have been shown to play critical roles in controlling embryonic growth and development. 5,6 Some imprinted genes are also known to encode DNA-binding proteins, such as Zac1 and Peg3. 7,8 The DNA-binding protein encoded by Zac1 binds to the 3 0 enhancer of H19 as a transcriptional activator, suggesting a functional connection between the 2 imprinted genes, paternally expressed Zac1 and maternally expressed H19.…”
Section: Introductionmentioning
confidence: 99%
“…Proper allelic expression of imprinted genes plays an important role in embryonic and neonatal growth, placental function, and postnatal behavior (2). Allele-specific DNA methylation at discrete regions established during gametogenesis defines the functional asymmetry of parental alleles (1).…”
mentioning
confidence: 99%